The cognitive aspect of interactive learning and teaching in visual arts education - Zlata Tomljenović (University of Maribor Press, 2020)
The task of contemporary visual arts education is to enable quality interaction among all subjects of the teaching process, through which the students are encouraged to think, imagine, and develop higher-order cognitive activities. The objective of this empirical research study was to verify the differences in the results of students in the control and experimental groups (n=285) regarding their knowledge and understanding of visual arts content. Analysis of the results shows that the students in EG showed significantly better results compared to the students in CG, which means that the interactive model of learning and teaching positively influenced the students' understanding of visual arts content.